Impact of Abiraterone Acetate plus Prednisone or Enzalutamide on Patient-reported Outcomes in Patients with Metastatic Castration-resistant Prostate Cancer: Final 12-mo Analysis from the Observational AQUARiUS Study - Thiery-Vuillemin, Antoine; Poulsen, Mads Hvid; Lagneau, Edouard; Ploussard, Guillaume; Birtle, Alison; Dourthe, Louis-Marie; Beal-Ardisson, Dominique; Pintus, Elias; Trepiakas, Redas; Lefresne, Florence; Lukac, Martin; Van Sanden, Suzy; et al. (European urology, 2020)
BACKGROUND: Few studies have examined patient-reported outcomes (PROs) with abiraterone acetate plus prednisone (abiraterone) versus enzalutamide in metastatic castration-resistant prostate cancer (mCRPC). OBJECTIVE: To determine the impact of abiraterone and enzalutamide on PROs. DESIGN, SETTING, AND PARTICIPANTS: AQUARiUS (NCT02813408) was a prospective, 12-mo, observational study in patients with mCRPC from Denmark, France, and the UK. INTERVENTION: Abiraterone or enzalutamide treatment according to routine practise. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: PROs were collected over 12 mo using Functional Assessment of Cancer Therapy-Cognitive Function (FACT-Cog), Brief Fatigue Inventory-Short Form (BFI-SF), Brief Pain Inventory-Short Form, and European Organisation for Research and Treatment of Cancer-Quality of Life Questionnaire (QLQ-C30) at baseline and routine visits. Outcomes included mean change in PROs, patients with clinically meaningful worsening (CMW) in PROs, and safety. Data were analysed using repeated measures linear and logistic models adjusted for baseline characteristics. RESULTS AND LIMITATIONS: Abiraterone-treated (N = 105) and enzalutamide-treated (N = 106) patients were included. Key PRO items (cognitive impairments and fatigue) were significantly (p < 0.05) in favour of abiraterone versus enzalutamide during the study. "Perceived cognitive impairment" and "comments from others" (FACT-Cog); "fatigue right now", "usual level of fatigue", and "worst level of fatigue" (BFI-SF); and "cognitive functioning" and "fatigue" (QLQ-C30) were significantly in favour of abiraterone over enzalutamide for three or more consecutive periods up to month 12. From study initiation, significantly fewer patients receiving abiraterone experienced one or more CMW episode in cognition and fatigue. Fatigue and asthenia (adverse events) were lower with abiraterone than with enzalutamide (5% vs 15% and 10% vs 11%, respectively). There were no treatment-related deaths. Limitations included lack of randomisation. CONCLUSIONS: In a real-world setting, this 12-mo analysis suggests an advantage of abiraterone acetate plus prednisone over enzalutamide on fatigue and cognitive function; this finding occurred early after treatment initiation. This difference should be considered when choosing treatment. PATIENT SUMMARY: This study looked at the effect of two treatments (abiraterone acetate plus prednisone and enzalutamide) for metastatic castration-resistant prostate cancer on patient quality of life over 12 mo. Using established questionnaires, patients reported that they experienced less fatigue and cognitive impairments (including memory loss and reduced thinking abilities) with abiraterone acetate plus prednisone than with enzalutamide.
Keywords: Abiraterone; AQUARiUS; Prospective Studies; senioři nad 80 let; metastázy nádorů; Humans; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Prednisone; Metastatic castration-resistant prostate cancer; prospektivní studie; Aged, 80 and over; Antineoplastic Agents; Enzalutamide; protinádorové látky; fenylthiohydantoin; Time Factors; Nitriles; mužské pohlaví; prednison; Benzamides; Abiraterone Acetate; Neoplasm Metastasis; časové faktory; Phenylthiohydantoin; hodnocení výsledků péče pacientem; Patient Reported Outcome Measures; Patient-reported outcomes; nádory prostaty rezistentní na kastraci; nitrily; abirateron; benzamidy; lidé; Aged; Prostatic Neoplasms, Castration-Resistant; senioři; Male; Quality of life